Armadillo (dasypus spp.) density through use of camera trapping and burrow density in French Guiana - Schaub, Roxane (2022)
Armadillo density estimates are important for species knowledge, but they are unknown in the Guiana Shield. We aimed at estimating Dasypus density through burrow density and camera trapping. We surveyed and trapped burrows in three protected sites in French Guiana, on strip transects covering 4.8 ha in each site, and estimated Dasypus density taking into account burrow measures and occupancy. Population densities ranged between 7.6 and 48.6 animals/km2 for Dasypus sp. nov. and 10.3 and 34.7 animals/km2 for D. kappleri. Dasypus density estimates through burrow survey and exclusive burrow entrance camera trapping is relatively low-cost, non-invasive and reliable.